Biomarkers associated with vulnerable plaques. (3rd October 2022) - Sharma, T; Maehara, A; Ben-Yehuda, O; Maeng, M; Kjoller-Hansen, L; Engstrom, T; Matsumura, M; Frobert, O; Persson, J; Wiseth, R; Larsen, A I; James, S K; et al.
Abstract: Background: Cardiovascular heart disease is the leading cause of mortality worldwide, with the rupture or thrombosis of an atherosclerotic plaque being the main reason behind an acute coronary syndrome. It has already been established that the morphology of atherosclerotic plaques determine their stability. A lipid rich lesion with a thin fibrous cap is more prone to rupture compared to solid fibrous lesions. In the PROSPECTII study we used Near infrared spectroscopy (NIRS) and Intravascular ultrasound (IVUS) to identify atherosclerotic plaques in the coronary arteries; NIRS-derived lipid core burden index (LCBI) and IVUS-derived plaque burden (PB) identified plaques that caused adverse cardiovascular events. Purpose: Our aim is to find biomarkers associated with LCBI or PB, to understand the development of vulnerable plaques. Methods: 902 patients were enrolled in this study after successful percutaneous coronary intervention (PCI). A combined NIRS-IVUS catheter was then used to analyze approximately 200m of coronary arteries. Blood samples for biomarker analysis were taken before the PCI procedure and plasma levels of 182 proteins associated with cardiovascular disease were assessed using a novel method for measuring proximity extension assay. Adjusted linear regression models were calculated between the biomarkers and the outcomes of interest, followed by a false discovery rate (FDR) correction. Results: We found 24 proteins associated with plaque burden and 28 proteins associated with LCBI after using a cut off of two tailed P value <0.05. An overlap of 8 biomarkers could be seen between the two groups. After adjusting the P values with FDR, Angiopoeitin like 3 (ANGPTL3) retained its association to LCBI, and Interleukin 18 receptor 1 (IL18R1) and colony stimulating factor 1 (CSF-1) to plaque burden. Conclusion: We were able to identify different biomarker patterns associated with plaque burden compared to lipid rich vulnerable plaques. ANGPTL3 was shown to only have an association with lipid rich plaques and not with solid fibrous lesions which further supports its role in vulnerable plaques. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Abbott Vascular, Infraredx, and The Medicines Company